Disparities in osteoporosis treatments. Issue 2 (February 2016) - Liu, Z.; Weaver, J.; Papp, A.; Li, Z.; Martin, J.; Allen, K.; Hui, S.; Imel, E.
Abstract Summary Osteoporosis treatment rates within 2 years following an index event (fragility fracture, osteoporotic bone mineral density (BMD) T-score, or osteoporosis ICD-9 codes) were determined from 2005 to 2011. Most patients were not treated. Fracture patients had the lowest treatment rate. Low treatment rates also occurred in patients that were male, black, or had non-commercial insurance. Introduction Clinical recognition of osteoporosis (osteoporotic BMD, assignment of an ICD-9 code, or the occurrence of fragility fractures) provides opportunities to treat patients at risk for future fracture. Methods A cohort of 36, 965 patients was identified from 2005 to 2011 in the Indiana Health Information Exchange, with index events after age 50 of either non-traumatic fractures, an osteoporosis ICD-9 code, or a BMD T-score ≤ −2.5. Patients with osteoporosis treatment in the preceding year were excluded. Medication records during the ensuing 2 years were extracted to identify osteoporosis treatments, demographics, comorbidities, and co-medications. Predictors of treatment were evaluated in a multivariable logistic regression model. Results The cohort was 78 % female, 11 % black, 91 % urban-dwelling, and 53 % commercially insured. The index events were as follows: osteoporosis diagnosis (47 % of patients), fragility fracture (44 %), and osteoporotic T-scores (9 %). Within 2 years after the index event, 23.3 % received osteoporosis medications (of which, 82.2 % were oral bisphosphonates). Treatment rates were higher after osteoporosis diagnosis codes (29.3 %) or osteoporotic T-score (53.9 %) than after fracture index events (10.5 %) (p < 0.001). Age had an inverted U-shaped effect for women with highest odds around 60–65 years. Women (OR 1.86) and non-black patients (OR 1.52) were more likely to be treated (p < 0.001). Patients with public (versus commercial) insurance (OR 0.86, p < 0.001) or chronic comorbidities (ORs about 0.7–0.9, p < 0.001) were less likely to be treated. Conclusion Most osteoporosis treatment candidates remained untreated. Men, black patients, and patients with fracture or chronic comorbidities were less likely to receive treatment, representing disparity in the recognition and treatment of osteoporosis.